2017
DOI: 10.1103/physrevlett.119.138101
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Chromosome Looping via Molecular Slip Links

Abstract: We propose a model for the formation of chromatin loops based on the diffusive sliding of a DNA-bound factor which can dimerise to form a molecular slip-link. Our slip-links mimic the behaviour of cohesin-like molecules, which, along with the CTCF protein, stabilize loops which organize the genome. By combining 3D Brownian dynamics simulations and 1D exactly solvable non-equilibrium models, we show that diffusive sliding is sufficient to account for the strong bias in favour of convergent CTCF-mediated chromos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 49 publications
4
142
0
Order By: Relevance
“…The LE model (Fudenberg et al, 2016;Goloborodko et al, 2016;Sanborn et al, 2015) quantifies another interesting scenario of chromatin folding, where an active motor (e.g., Cohesin) binds to DNA and actively extrude a DNA loop up to encountering oppositely oriented CTCF anchoring sites. A variant of the LE, the Slip-Link model proposes a similar scenario based on random sliding of the loop bridging sites, without requiring an active, energy burning mechanism (Brackley et al, 2017). Importantly, both the LE and the SL models describe well folding at loci where CTCF is the main driving force and are consistent with the CTCF convergence bias (Brackley et al, 2017;Sanborn et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The LE model (Fudenberg et al, 2016;Goloborodko et al, 2016;Sanborn et al, 2015) quantifies another interesting scenario of chromatin folding, where an active motor (e.g., Cohesin) binds to DNA and actively extrude a DNA loop up to encountering oppositely oriented CTCF anchoring sites. A variant of the LE, the Slip-Link model proposes a similar scenario based on random sliding of the loop bridging sites, without requiring an active, energy burning mechanism (Brackley et al, 2017). Importantly, both the LE and the SL models describe well folding at loci where CTCF is the main driving force and are consistent with the CTCF convergence bias (Brackley et al, 2017;Sanborn et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…Albeit diffusion is the origin of loop formation within the SL, technically the model describes an off-equilibrium system, because of the envisaged adsorbing boundary anchors. Computer simulations have shown that the SL model not only explains the CTCF convergence bias, but also well accounts for the size distribution of CTCF-based loops, as derived by ChIA-PET data (Brackley et al, 2017).…”
Section: The Slip-link Modelmentioning
confidence: 87%
See 3 more Smart Citations